Pathogenic Variability in Isolates of Fusarium Oxysporum F. SP. Ciceris - Al-Taae, Ali Kareem; Al-Jobory, Saleh Ahmed Eesa (Science Journal of University of Zakho, 2013)
Twenty isolates of Fusarium oxysporum f. sp. ciceris were isolated from wilted chickpea plants obtained from different districts of north part of Iraq to assess variability in pathogenecity of the populations. Each isolate was tested on 12 differential chickpea varieties . Isolates showed highly significant variation in wilt severity on the differential varieties . Based on the reaction types that induced on differential varieties, isolates were grouped into four groups, First group included isolates FocS1 , FocQ7 , FocQ10 , FocF13 , FocH17 and FocH18 The Second group included isolates FocS2 , FocS3 , FocS4 , FocQ5 , FocQ8 , FocQ9 , FocF11 , FocF12 , FocF14 and FocH19 The Third group included isolates FocF15 , FocH16 , FocH20 .Where the isolate FocQ6 was placed in the Fourth group .Results showed that the percentage of genetic similarity was ranged 42% to 100% and was 42% between the first group and other groups and 72% between the three groups the rest and thus this indicate the presence of four races of the fungus which are zero, 4, 5, and 1B / C this represent the first record of these races in Iraq.